Experimental and computational investigation of a latent heat energy storage system with a staggered heat exchanger for various phase change materials. (September 2018) - Koukou, Maria K.; Vrachopoulos, Michalis Gr.; Tachos, Nikolaos S.; Dogkas, George; Lymperis, Kostas; Stathopoulos, Vassilis
Highlights: A Latent Heat Thermal Energy Storage system utilizing a staggered heat exchanger was tested. All four organic phase change materials studied as thermal storage materials show a super cooling effect. Super cooling effect of phase change materials affected the operation and performance of the heat exchanger studied. Heat transfer mechanism strongly affects the energy storage process and performance. Energy storage system operation needs optimization according to thermal storage materials properties. Abstract: This work reports the operation of a Latent Heat Thermal Energy Storage system (LHTES) utilizing a staggered heat exchanger (HE) and using various organic Phase Change Materials (PCMs). In a LHTES test rig set measurements regarding energy storage and release were performed in the working temperature range of each Phase Change Material. Nominal melting temperatures of the PCMs used were 40–53 °C. Computational Fluid Dynamics (CFD) simulation was applied to follow the operation of the test rig. The test rig consisted of a compact insulated tank, filled with PCM, a staggered heat exchanger to supply or extract thermal energy by the PCM and a water pump to circulate water as a Heat Transfer Fluid (HTF). Different HTF flow rates affect charging (melting) and discharging (solidification) processes but more significant was the effect of heat transfer mechanisms occurring. The latter was confirmed by inserting buoyancy currents created due to convection in a CFD simulation program where melting time was reduced compared to the same conditions with only conduction occurring. The suggested LHTES configuration is a promising compact unit despite the PCMs thermal resistance and solidification hysteresis phenomena, as well as the heat transfer mechanism strongly affecting the energy storage process.